2016
DOI: 10.1016/j.bpj.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Membrane Transport Activity and Death of Cells via Electroosmotic Manipulation

Abstract: Although the volume of living cells has been known to heavily influence their behavior and fate, a method allowing us to control the cell size in a programmable manner is still lacking. Here, we develop a technique in which precise changes in the cellular volume can be conveniently introduced by varying the voltage applied across a Nafion membrane that separates the culture medium from a reservoir. It is found that, unlike sudden osmotic shocks, active ion transport across the membrane of leukemia K562 cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Moreover, extracellular osmolarity or modification of specific ion concentrations strongly impacts the mechanical properties of the cell through cell volume changes that may affect various cellular processes (e.g. mitosis, mitochondrial functions and DNA repair) 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extracellular osmolarity or modification of specific ion concentrations strongly impacts the mechanical properties of the cell through cell volume changes that may affect various cellular processes (e.g. mitosis, mitochondrial functions and DNA repair) 1519 .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 This suggests that the observed surface undulation of tumor cells may be caused by associated cytoskeleton and adhesion dynamics inside. [40][41][42] On the other hand, recent evidence has also demonstrated that slow changes in the cellular volume can be triggered by active cross-membrane transport of water and ion molecules, 19,[43][44][45][46] which could also lead to the surface undulation of cells. Further investigations are certainly Fig.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Interestingly, recent evidence has indicated that the invasiveness of tumor cells is intimately related to their physical characteristics. For example, it was found that invasive epithelial cells are generally soer, as well as more capable to undergo shape changes, than those with low metastatic potential [19][20][21] both in cell lines and clinical samples from non-small cell carcinoma of the lung, breast ductal adenocarcinoma, and pancreatic adenocarcinoma. 22,23 Along this direction, the use of deep learning method to relate the physical response of cells to different cancer biomarkers [11][12][13] has received increasing attention, with the vision of achieving precision oncology eventually.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that AQP3 affects the Wnt/GSK-3β/β-catenin pathway in liver CSCs (LCSCs), and modulates their stemness, differentiation, and apoptosis [ 135 ]. Other studies have identified AQP4 as the most abundant AQP in nasopharyngeal and lung CSCs and have shown its involvement in the regulation of large volumetric changes related to an increase in death rate [ 155 ]. Using a novel electro-osmotic microfluidic system that controls cell osmolarity gradients, AQP4 expression has been shown to be directly correlated with the speed of cell migration [ 137 ] ( Table 3 ).…”
Section: Physiological Roles Of Aqps In Driving Msc Functionmentioning
confidence: 99%